Dinâmica de populações: uma proposta de prática investigativa para o ensino médio com o caruncho dos grãos, Sitophilus sp. (Hexapoda; Coleoptera; Curculionidae) - Deiverson Roberto da Silva (2021)
When working on the contents of ecology, it is possible to notice that students in general limit themselves to decorating ecological concepts and interactions, so they are unable to relate what is learned in the classroom to real everyday situations. Today humanity is experiencing the biggest health crisis in its history, knowing concepts about ecology, how to apply them and recognizing itself as a thread in this huge web becomes urgent in the face of the challenges imposed by historically fragmented thinking. Investigative experimental activities can increase student interest in classes, contextualize content to students' reality and give meaning to what is taught. The present work deals with the production of a practical investigative didactic sequence with insects, for the high school of a public school in Ribeirão das Neves - MG. An investigative didactic sequence –IDS– was proposed where students will perform an experiment with the insect Sitophilus sp. observing the influence of temperature on the growth of the insect population of this genus. In addition to knowing some of the characteristics of scientific production, from the perspective of scientific literacy, with an emphasis on argumentative practices, with the product an - IDS - and the creation of an experiment with insects in the content of ecology. With IDS's proposal, it was possible to observe that didactic work with insects is little used in science and biology classes. The experiment carried out for the IDS proposal demonstrated that insects can be used in experimental classes in the teaching of Ecology, either in laboratories, in the classroom, or even in their natural habitat. The didactic use of insects allows the collection of results in a relatively short time, with low costs, and without the need for a formal laboratory, since the insects can be stored in containers that take up little space.